Stress-induced reactive oxygen species compartmentalization, perception and signalling - Castro, Bardo; Citterico, Matteo; Kimura, Sachie; Stevens, Danielle M; Wrzaczek, Michael; Coaker, Gitta (Nature plants, 2021)
Reactive oxygen species (ROS) are essential for life and are involved in the regulation of almost all biological processes. ROS production is critical for plant development, response to abiotic stresses and immune responses. Here, we focus on recent discoveries in ROS biology emphasizing abiotic and biotic stress responses. Recent advancements have resulted in the identification of one of the first sensors for extracellular ROS and highlighted waves of ROS production during stress signalling in Arabidopsis. Enzymes that produce ROS, including NADPH oxidases, exhibit precise regulation through diverse post-translational modifications. Discoveries highlight the importance of both amino- and carboxy-terminal regulation of NADPH oxidases through protein phosphorylation and cysteine oxidation. Here, we discuss advancements in ROS compartmentalization, systemic ROS waves, ROS sensing and post-translational modification of ROS-producing enzymes and identify areas where foundational gaps remain.
Keywords: Arabidopsis; Stress, Physiological; reaktivní formy kyslíku; Reactive Oxygen Species; Signal Transduction; fyziologický stres; signální transdukce